Winners and losers in bank resolution: Recent examples and a modest reform proposal - Benoît Cœuré; Elke König; Jan Pieter Krahnen; Harry Huizinga; Jonas Schlegel (Leibniz Institute for Financial Research SAFE, 2024)
In 2023, both the US and Europe witnessed banking crises, notably involving Silicon Valley Bank and Credit Suisse. Relevant authorities intervened to prevent contagion, and distressed banks were sold at seemingly deflated prices. We identify three primary factors contributing to elevated profits in distressed bank mergers, particularly in Europe: the absence of a robust backstop, ineffective use of the bail-in tool in loss allocation, and a lack of competition among bidders during the sale of distressed bank assets. These findings lead to concrete policy recommendations addressing backstop mechanisms, bail-in debt, and the strengthening of auction-like settings in asset sales. In the longer term, the European resolution framework and deposit guarantee system need to be transformed along the lines of the FDIC.
Keywords: 330; Bank Resolution; Bank Acquisition; SRM; FDIC